DEVELOPMENT OF LEARNING VIDEOS TO IMPROVE STUDENT 'S LEARNING OUTCOMES IN IPS CLASS VIII JUNIOR HIGH SCHOOL 6 PARIAMAN - Aulia Putri Rahman; Salman M Noer; Nela Sari Yolanda (LPPM Ekasakti University, 2022)
This study aims to determine student learning outcomes with the help of learning video media in Social Studies subjects for Class VIII SMPN 6 Pariaman for the 2021/2022 academic year . and ASEAN. This type of research is development research known as Research And Development (R&D), using the ADDIE development model. The results showed that the learning video met the very valid criteria with the average acquisition result of 3.63%. The results of the practicality assessment of the teacher's response with an average of 88.12% in the very practical category and the results of the practicality assessment of the student's response with an average of 84.04% in the very practical category. While the effectiveness of the learning video obtained t-count results of 5,618 which is in very good qualification. The value of t count is greater than t table so that H0 is rejected and H1 is accepted. So there is a significant difference in student learning outcomes of Social Sciences between before and after using learning media. It was concluded that the learning videos on the materials of Interspatial Advantages and Limitations and Their Influence on Economic, Social, Cultural Activities in Indonesia and ASEAN that had been developed were declared valid, practical and effective for use in social studies learning.